Perfil de ácidos grasos en aceites de cocina de mayor venta en Medellín-Colombia (2014)
ABSTRACT: Fatty acids profile in cooking oils has repercussions on human health. Objective: To determine fatty acids profile in cooking oils used at home, before frying. Materials and methods: 14 different commercial oil brands (from olive, canola, sunflower oil, and mixtures) were selected according to sells reported by a hypermarket in Medellín-Colombia. Fatty acids profile was determined by gas chromatography and differences between oils were analyses. Results: Compared with other brands, mixture oils had the highest percentage of saturated fatty acid (16,9±1,5%) (p=0,02); olive and canola oils the highest percentage of monounsaturated, 78,1±0,4% and 62,4±0,7% respectively(p=0,01); mixtureandsunflower oils hadthe highest percentage of polyunsaturated, 54,7±2, 4% and 52,4±5,2 respectively (p=0,02). Palmitic (saturated), oleic (monounsaturated), and linoleic acids (polyunsaturated) were the predominant fatty acids found in all oils. Canola oil had the highest content of α-linolenic acid (8,1±1,5%) (p=0,04), the biggest relation between unsaturated and saturated fatty acids (12,0±0,1%) (p=0,02), and the lowest relation between linoleic and linolenic acid (2,4±0,4%) (p=0,02). Range of trans fatty acid content was 0,9±0,9 to 1,8±1,3% without differences between brands (p=0,17). Conclusions: Canola oils had the best fatty acid profile based on: α-linolenic content, unsaturated/saturated ratio and linoleic/ linolenic acid ratio.